Spatial and temporal distributions of rainfall and EI30 values in Pulau Pinang, Peninsular Malaysia - Shamshad, A.; Wan Hussin, W.M.A.; Sanusi, S.A.M.; Isa, M.H. (2006)
Soil erosion is a serious problem for the agriculture land use in Malaysia and many other parts of the world. In most of the countries, Revised Universal Soil Loss Equation (RUSLE) is the popular model for predicting the soil losses in runoff from specific field areas in specific cropping and management system. Rainfall erosivity factor (R) is one of the important parameters of this model. As suggested in the past, the R factor or EI30 values should be computed from the long term, continuous pluviographic records. There is a lack of such kind of data in the world including Malaysia. In contrast daily, monthly and other long interval rainfall data are available at wider scale. In the present study, an attempt has been made to develop rainfall erosivity models using pluviographic data of six stations. The models can be used to compute rainfall erosivity using monthly rainfall data. Using the equations, the EI30 values were evaluated at other stations using monthly rainfall data. The result showed that the mean annual rainfall in the area varied from about 2200 mm to 3900 mm. The corresponding R-factor ranged from about 9,000 to 14,000 MJ mm ha-1 hr-1 year-1. For these tropical sites, both rainfall and EI30 values are highly seasonal with two peaks, in general, in the months of April and October.